The Design of Boarding School in Simanindo, Samosir (Green Architecture) - Angela Fricilia Sagala; Imam Faisal Pane (International Journal of Architecture and Urbanism, 2021)
Simanindo is one of the priority areas that is the heart of tourist destinations on Lake Toba because of the potential for beautiful landscapes, cultural heritage, and city landmarks that show the existence of Toba Batak culture. In terms of the education sector, Simanindo residents generally complete primary and secondary education. This is because the educational infrastructure in the Simanindo sub-district is inadequate. Boarding schools can be a solution to educational problems in Simanindo District with a design concept that uses a green architectural approach to create a school that is energy efficient, safe, and environmentally friendly. The data collection method used is qualitative that collects the data and information about the condition directly from the community about the behavior observed in the region thoroughly, a field survey and then clarified with image and video documentation, as well as by collecting secondary data through studies and case study literature. Boarding School in Simanindo, Samosir Regency as an energy efficient and environmentally friendly school by maximizing the use of natural lighting and ventilation, reducing the use of chemicals, and maximizing the use of local vegetation in accordance with the context of the surrounding environment which is dominated by the function of green open spaces. This research is expected to be able to explain the application of green architecture in educational buildings that can create energy-efficient buildings and follow the cultural context in the surrounding environment.